Sensory and Consumer Studies in Plant Breeding: A Guidance for Edamame Development in the U.S. - Carneiro, Renata C. V.; Duncan, Susan E.; O'Keefe, Sean F.; Yin, Yun; Neill, Clinton L.; Zhang, Bo (Frontiers in Sustainable Food Systems, 2020)
Plant breeding is an important discipline to develop food products and improve overall quality, chemical composition, and nutritional value of crops, vegetables, fruits, and nuts, which can be important allies in health promotion. Apples, blueberries, wine grapes, tomatoes, and peanuts are a few examples of food products that were improved in past decades through plant breeding programs in the United States. Recently, edamame (vegetable soybean) has gained special attention from breeders, non-breeder researchers, growers, and consumers, and new edamame varieties are currently being developed for domestic production. As a popular nutritious crop in Asian countries, edamame is increasing in sales and consumption in the United States. Therefore, edamame has great potential to be a profitable alternative crop to replace tobacco farming, whose production and market value have been declining. Until the present date, most published reviews on edamame have focused on its agronomic characteristics. However, understanding consumer expectations, needs, and acceptability for new and improved crops like edamame is vital to guide and sustain their production. It is important that researchers working on plant breeding programs understand and consider the aspects that are relevant for both growers and consumers (e.g., crop productivity, pest and disease resistance, nutritional properties, and sensory attributes). Thus, this review paper aims to integrate available information on sensory quality of edamame and to support its development and production in the United States. This review presents an overview of how sensory evaluation and consumer studies have been used to support plant breeding programs in the development of alternative crops, such as edamame.